Unveiling Hangzhou’s Intellectual Legacy: Chinese Buddhist Reference Works and Knowledge Production in the Song and Beyond - Baskind, James (Religions, 2023)
This article explores Hangzhou’s multifaceted role in shaping Chinese Buddhist culture and contributing to knowledge production. As a vital hub of Chinese material and intellectual culture, Hangzhou’s significant contributions to Buddhism are emphasized, shedding light on its key role in disseminating Buddhist teachings and preserving knowledge. The study delves into the rich history of Buddhist reference works, particularly leishu, showcasing how these compilations were pivotal in organizing and transmitting Buddhist wisdom. The article connects Hangzhou’s intellectual legacy to the broader context of Chinese Buddhism, emphasizing its crucial position in the development and dissemination of Buddhist doctrines. Additionally, it highlights ongoing academic efforts to compile an Encyclopedia of Hangzhou Buddhist Culture, underscoring Hangzhou’s continued importance in contemporary Buddhist scholarship.